The current state of investigation and new finds of melanosporoid fungi in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The general characteristics of melanosporoid fungi and results of a critical revision of data about the representatives of this group known from Ukraine are presented. As a result of generalization of the obtained data with the results of our research a preliminary conspectus of biota which consists of eleven species is made. Of these, Persiciospora moreaui and Syspastospora parasitica are provided in Ukraine for the first time.
Keywords: Melanospora spp., Persiciospora moreaui, Syspastospora parasitica, distribution, fungicolous properties, mycoparasitism.